Entre a indeterminação da vida e o direito à cidade na periferia: estudo de ações coletivas nas ocupações da CIC - Sanches, Aline (2021)
This paper aims to analyze to what extent the resistance – practices, strategies, and the action of residents that live and external entities that work in the occupations in CIC – contribute to the reproduction of life and/or to the promotion of the right to the city on the periphery. Urban conflicts are the central point. They are understood from the perspective that they are likely to evince practices and experiences that approach the right to the city as a form of resistance, with the prospect of claiming a city yet to be produced. At first, this paper addresses the unequal production of the urban space in Curitiba, to understand how the precariousness weakens the notion of social rights. However, amidst the dispossessions and the indetermination of life in the periphery, the residents seek to ensure their survival and to build experiences, starting from the everyday life and producing forms of resistance. Through the study of the entities’ key actors, it is analyzed how and to what extent these groups can produce urban resistance to promote the right to the city. Seeking to discuss these issues, the paper uses the CIC occupations as a Case Study. For the development of the research, time frames were defined, directing to the reconstruction of the occupation after a fire occurred at the end of 2018 and to the pandemic period in 2020. Therefore, the entities that acted in these two moments were identified, selected, and interviewed. Through the interviews, it was noticed that, sometimes, the notion of the right to the city is strict to the house and infrastructure. However, the established relations of confidence help in the experimentation and production of the city. The practices can indicate an ambiguous relationship that goes from conformism to resistance, as people conform to situations of blame and precariousness on the periphery and embrace the unequal city. However, they are also an active presence in the pursuit of land ownership and in the insurgencies of everyday life.